Deletion of L4 domains reveals insights into the importance of ribosomal protein extensions in eukaryotic ribosome assembly - Gamalinda, Michael (Cold Spring Harbor Laboratory Press, 2014)
Numerous ribosomal proteins have a striking bipartite architecture: a globular body positioned on the ribosomal exterior and an internal loop buried deep into the rRNA core. In eukaryotes, a significant number of conserved r-proteins have evolved extra amino- or carboxy-terminal tail sequences, which thread across the solvent-exposed surface. The biological importance of these extended domains remains to be established. In this study, we have investigated the universally conserved internal loop and the eukaryote-specific extensions of yeast L4. We show that in contrast to findings with bacterial L4, deleting the internal loop of yeast L4 causes severely impaired growth and reduced levels of large ribosomal subunits. We further report that while depleting the entire L4 protein blocks early assembly steps in yeast, deletion of only its extended internal loop affects later steps in assembly, revealing a second role for L4 during ribosome biogenesis. Surprisingly, deletion of the entire eukaryote-specific carboxy-terminal tail of L4 has no effect on viability, production of 60S subunits, or translation. These unexpected observations provide impetus to further investigate the functions of ribosomal protein extensions, especially eukaryote-specific examples, in ribosome assembly and function.